Aproximación de Bragg-Williams aplicada al estudio de la electrosorción en un electrodo modificado - Pasinetti, Pedro Marcelo (2019)
In this work is presented the Bragg-Williams mean field theoretical approach to study the electrosorption phenomena on a modified electrode. The electrode surface is modified by the irreversible pre-adsorption of a non-electroactive species, which is capable of blocking a fraction of the surface adsorption sites. Then, a second electroactive species is adsorbed on the empty sites. Interspecies lateral interactions are considered. The adsorption/ desorption process involves charge transfer, that is, when a particle A is adsorbed, an electron is transferred to the electrode surface. The analysis is based on the study of adsorption isotherms and voltammograms, considering different interaction energies and impurities concentrations. The theoretical approximation is contrasted with Monte Carlo results and experimental data.